Towards the voluntary adoption of integrated reporting: Drivers, barriers, and practices - Cecília Carmo; Inês Correia; Joaquim Leite; Amélia Carvalho (Administrative Sciences, 2023)
Integrated reporting is essentially a voluntary practice worldwide. For this reason, although it is growing, its diffusion is slow. Based on the Portuguese context, where a reduced number of listed companies publish integrated reports, this study aims to explore the drivers and barriers for the voluntary adoption of integrated reporting and the reporting practices up to the production of an integrated report. To this end, an analytical framework based on the Diffusion of Innovation Theory was developed and applied to data collected from a survey and corporate reports from both "adopters" and "non-adopters". The evidence collected suggests that the adoption of integrated reporting may be driven by the perception of a relative advantage over traditional reporting in terms of providing more relevant information to capital providers, particularly banks. The publication of an integrated report appears to be the result of a process of incremental improvements in the practice of disclosure and assurance of non-financial information, so that the previous experience with sustainability reporting is also an important driver for voluntary integrated reporting. Finally, companies may be differently prepared for transition to integrated reporting and, therefore, have different perceptions of its cost and complexity, which may act as a barrier.
Keywords: 350; <IR>~framework; IIRC; integrated report; Portugal; sustainability reporting; voluntary disclosure